ERA-40 2.5 Degree Surface and Flux Data - European Centre For Medium-Range Weather Forecasts (UCAR/NCAR - Research Data Archive, 2004)
The 6-hourly surface and flux data on global 2.5 degree grids from the ECMWF ERA-40 reanalysis project are in this dataset.